2017
DOI: 10.14814/phy2.13314
|View full text |Cite
|
Sign up to set email alerts
|

Daily rhythms of cloacal temperature in broiler chickens of different age groups administered with zinc gluconate and probiotic during the hot-dry season

Abstract: The aim of the experiment was to evaluate effects of zinc gluconate (ZnGlu) and probiotic administration on the daily rhythm of cloacal temperature (t cloacal) in broiler chickens of different age groups during the hot‐dry season. One‐day‐old broiler chicks (n = 60) were divided into groups I–IV of 15 chicks per group, and treated for 35 days: Group I (control) was given deionized water; Group II, ZnGlu (50 mg/kg); Group III, probiotic (4.125 × 106 cfu/100 mL), and Group IV, ZnGlu (50 mg/kg) + probiotic (4.125… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
1
18
0
3
Order By: Relevance
“…Of the three seasons in the zone, the cold‐dry and hot‐dry seasons have been described as thermally stressful to livestock (Aluwong et al. ). Environmental parameters that adversely affect livestock performance and health are ambient temperature (AT), relative humidity (RH), thermal radiation, and air speed (Sevi and Caroprese ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the three seasons in the zone, the cold‐dry and hot‐dry seasons have been described as thermally stressful to livestock (Aluwong et al. ). Environmental parameters that adversely affect livestock performance and health are ambient temperature (AT), relative humidity (RH), thermal radiation, and air speed (Sevi and Caroprese ).…”
Section: Introductionmentioning
confidence: 99%
“…The Northern Guinea Savannah zone of Nigeria is characterized by three distinct seasons, namely: the cold-dry, hot-dry, and the rainy seasons (Dzenda et al 2011;Ayo et al 2014). Of the three seasons in the zone, the cold-dry and hot-dry seasons have been described as thermally stressful to livestock (Aluwong et al 2017). Environmental parameters that adversely affect livestock performance and health are ambient temperature (AT), relative humidity (RH), thermal radiation, and air speed (Sevi and Caroprese 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In broiler breeds, younger birds could be more resilient to higher thermal environments than older ones. Cloacal temperature during daytime was age-dependently higher in broilers (38). Vale et al (19) reported that there was no impact of heat waves in broilers aged between 29 and 31 days, but increased mortality was found in broilers older than 31 days when the maximum THI was above 30.6 • C, the main feature of days presenting heat wave.…”
Section: Discussionmentioning
confidence: 99%
“…Regiões localizadas em ambientes tropicais que apresentam elevada radiação solar, alta temperatura e baixa umidade relativa do ar ao longo do ano, são fatores limitantes para o setor agropecuário da avicultura, culminando assim, em níveis excessivos de estresse por calor. Condições adversas como estas ocasionamdeclínio de rendimento ou até morte dos animais devido a diminuição do bem-estar e a saúde das aves, acarretando também em danos fisiológicos das mesmas (Aluwong et al, 2017).…”
Section: Introductionunclassified
“…Os índices climáticos são de extrema importância para o entendimento do conforto térmico dos animais sob as condições locais, auxiliando na construção de abrigos de produção, dieta dos animaisou nas tomadas de decisões das indústrias avícolas (Angelo;Naas;Vendrametto, 2014;Aluwong et al, 2017 devido ao material de cobertura do galpão sofrendo influência também da baixa incidência de radiação solar direta sobre o mesmo.…”
Section: Introductionunclassified